Dlaczego warto rozwijać u dziecka zdolność do czytania i ekspresji emocji? Refleksja z badań własnych muzykoterapeuty = Why develop child`s ability to grow to read and express emotions? Reflection from the researcher`s own music therapist - Szymajda, Agnieszka (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The article presents issues related to the ability to support the development of competence of reading and expressing emotions in children aged 4-7 in music therapy. Based on literature, the article discusses issues related to the emotional development of children aged 4-7, especially the competence of reading and expressing emotions.
Keywords: muzykoterapia; dziecko w wieku przedszkolnym; czytanie emocji; ekspresja emocji; music therapy; preschool children; reading emotions; expressing emotions